Generalised Joint Hypermobility in Caucasian Girls with Idiopathic Scoliosis: Relation with Age, Curve Size, and Curve Pattern - Dariusz Czaprowski (The Scientific World Journal)
The aim of the study was to assess the prevalence of generalised joint hypermobility (GJH) in 155 girls with idiopathic scoliosis (IS) (age 9–18 years, mean 13.8 ± 2.3). The control group included 201 healthy girls. The presence of GJH was assessed with Beighton (B) test. GJH was diagnosed in 23.2% of IS girls and in 13.4% of controls (P=0.02). The prevalence of GJH was significantly (P=0.01) lower in IS girls aged 16–18 years in comparison with younger individuals. There was no difference regarding GJH occurrence between girls with mild (11–24°), moderate (25–40°), and severe scoliosis (>40°) (P=0.78), between girls with single thoracic, single lumbar, and double curve scoliosis (P=0.59), and between girls with thoracic scoliosis length ≤7 and >7 vertebrae (P=0.25). No correlation between the number of points in B and the Cobb angle (P=0.93), as well as between the number of points in B and the number of the vertebrae within thoracic scoliosis (P=0.63), was noticed. GJH appeared more often in IS girls than in healthy controls. Its prevalence decreased with age. No relation between GJH prevalence and curve size, curve pattern, or scoliosis length was found.